Work Design and Professional Practices of Community Health Cadres in Adapting to Changes in Minimum Service Standards: A Capacity Building Perspective - Lindanur Sipatu; Wisra M; Abdul Azis R; Sitti Aminah; Ayu Putri Utami (Journal of Educational Management Research, 2026)
This study aims to explore the understanding and experiences of community health cadres in carrying out public health service tasks amid changes in minimum service standards. This research employed a qualitative approach using a case study design. Data were collected through in-depth interviews with 19 informants and analyzed using the Interactive Analysis Model supported by NVivo 12 Plus for Windows. The findings reveal that health cadres experience excessive workloads due to increasing task demands that must be completed within limited timeframes, while the compensation received remains below expectations. At the same time, cadres are required to meet increasingly complex work standards in line with the development of primary health care policies. These conditions heighten the risk of burnout and negatively affect the quality of services delivered to the community. In addition, cadres’ competencies and communication skills in providing health services have not yet reached an optimal level. The practical implications of this study emphasize the importance of strengthening health cadre professionalism through clear and well-structured work design, supported by capacity building, training, and continuous professional development as key dimensions of educational management to improve service quality sustainably.